Community health worker's perceptions (CHWS) of their role in Primary Health Care of Ga-Segonyana rural community - Mkhondwane, Ann (My University, 2019)
Background: Primary Health Care (PHC) is globally recognized as one of the effective strategies for the implementation of Sustainable Developmental Goals (SDGs). The global shortage of health care workers weakens the health care system, which impacts negatively in the achievement of universal health coverage and the SDGs. Community Health Workers (CHWs) are recognized as an integral resource in addressing the shortage of health workers in health care. In the rural villages of Ga-Segonyana, access to healthcare services remains a challenge and the use of CHWs to address the problem is strongly advocated. Aim: The study sought to explore the perceptions of community health workers (CHWs) of their role regarding the services they render to the community and their contribution towards strengthening PHC services in Ga-Segonyana local municipality. Methods: This study utilised an exploratory research design to conduct semi-structured interviews with nine purposefully selected CHWs in the Ga-Segonyana. All the interviews were translated from Setswana to English language and transcribed verbatim. Directed content analysis was used to analyse data from the transcribed interviews. Atlas ti computer software, version 7.0, was used for data analysis. . Results: Despite their lack of a written scope of work, the CHWs were able to outline their roles and responsibilities as expected by the employers. In terms of their work as CHWs, the results indicated that they have had both good and bad experiences. CHWs perceived the training received to be related to the nature of their work. However, there were no support systems to assist them with issues like psychological trauma and other pertinent situations in which they find themselves. The perceived barriers and challenges to CHWs pertain to ill-treatment to which they have been subjected by patients, lack of support systems, lack of recognition for their contribution, lack of training, lack of co-operation and collaboration from the relevant departments and organisations and other stakeholders, lack of resources and late payment of stipends. Conclusion: The study successfully explored the CHWs’ perceptions of their role on the services they render to the community and their contribution towards strengthening PHC services in the rural district of Ga-Segonyana. Understanding CHW roles will assist in examining how their roles might determine how they perform their daily tasks. So the study managed to highlight the importance of investing in CHWs for the empowerment of impoverished areas in South Africa.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirement for the degree Master of Public Health in Rural Health (May 2019)
Keywords: Primary health care; Health services; Community health services; Public health